The Mediating Role of Organizational Commitment in Relationship Between Workload and Compensation on Employee Performance - Ardiansyah, Herwin; Tridayanti, Hermien; Suyono, Joko; Setyowati, Denny (Universitas Muhammadiyah Gresik, 2025)
Oil and gas companies in the Bojonegoro city area, East Java are entering a period of very competitive business. One of the efficiency efforts carried out by the company is to employ the minimum number of workers possible but still provide maximum contribution according to the company's targets. This research aims to determine the influence of workload variables and compensation variables which have an impact on employee performance with organizational commitment as an intervening variable. The type of research used is quantitative research with the population in this research being all 33 employees. The sampling technique in this research used saturated sampling questionnaire data. The data analysis method uses Path Analysis using the Smart PLS version 3 application. The research shows that Workload (X1) has a negative influence on Employee Performance (Y), Compensation (X2) has insignificant influence on Employee Performance (Y), Workload (X1) has a negative influence on Organizational Commitment (Z), Compensation (X2) influences Organizational Commitment (Z) and Organizational Commitment (Z) influences Employee Performance (Y).